Analisa Pemasaran Platform P2P Lending Syariah pada PT Alami Fintek Sharia - Saifuddin Saifuddin; M Hadziq Affan (Universitas Muhammadiyah Surabaya, 2023)
This research is focused on the investatation marketing strategy of Peer to peer lending investment at PT. Alami Fintek Sharia (Alami). The purpose of this research is to improve the marketing strategy of the Fintech P2P (Alami) marketing platform to increase consumers in UMKM funding. The main theory is Marketing Mix (4P). The object of this research is the marketing strategy of the marketing team at PT. Alami Fintek Sharia (Alami). The research method used qualitative with a library research approach. The results of this research are the products that offered by Alami are different from other products and provide benefits for users so that users can attract consumers' purchasing power. The price offered is also affordable, this is also one of the attractions for consumers to help determinings their choice in investing using Alami.